Overview on the degradability of polymer nanocomposites - Pandey, JK; Reddy, KR; Kumar, AP; Singh, RP (Polymer Degradation and Stability, 2005)
Polymer nanocomposites have attracted great attention world wide from both academic and industrial points of view. The material properties of polymers can be enhanced dramatically by incorporating layered silicates at fairly low concentrations. The durability of any material depends upon several factors e.g. light, heat, microwaves, mechanical abrasion etc. The study and the effect of these factors on the performance are essentially required to extend the application limits. The durability of polymer nanocomposites has been evaluated under different environments. The present review describes the durability of different polymer nanocomposites mainly under thermal- and photoageing. Biodegradable nanoeomposites of different polymers are also discussed briefly. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Biodegradation; Degradation; layered silicates; Nanocomposites; weathering

Synthesis and biodegradability of polyaspartic acid: a critical review - Thombre, SM; Sarwade, BD (Journal of Macromolecular Science-Pure and Applied Chemistry, 2005)
Poly(aspartic acid) (PAA) being biodegradable is suitable for various industrial medical and agricultural applications to replace many non-biodegradable polymers in use. Poly(aspartic acid) can be synthesized by different methods with and without catalyst in different forms such as polysuccinimide, either hydrolyzed to acid or salt. The polymer of (aspartic acid) is present in different forms such as alpha, beta and L, D isomers. The conformational analysis of poly(aspartic acid) was done by various analytical methods. Different combinations of these two isomer present in different percentage can be detected by various methods such as Hoffman degradation, IR, and NMR spectroscopic analysis. From the standard test for biodegrad ability, it was shown that the polymer is fully biodegradable. In this review, synthesis and characterization of homo and copolymer derivatives of PAA, along with the application and biodegradability in comparison with the other polymer in use, is discussed briefly.
Keywords: Biodegradation; poly(aspartic acid); Polycondensation; polysuccinimide; synthesis; thermal

Biodegradation of gamma-sterilised biomedical polyolefins under composting and fungal culture environments - Alariqi, Sameh A. S.; Kumar, A. P.; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2006)
Polyolefin-based commodities are widely used as biomedical devices and food packaging after gamma-sterilisation. The aim of the present work was to study the effect of gamma-sterilisation on the biodegradation of polyolefins. Films of isotactic polypropylene, high-density polyethylene and ethylene-propylene (EP) copolymers were sterilised under gamma-radiation with doses of 10 and 25 kGy. Neat and sterilised samples were incubated in compost and fungal culture environments. The changes in functional groups, surface morphology and chain scission in polymer chains were characterized by FTIR spectroscopy, SEM and viscometric measurements, respectively. A gradual decrease in intrinsic viscosity [eta] and increase in carbonyl and hydroxyl regions in FTIR spectra were found for the gamma-sterilised samples as a function of increasing dose. Polypropylene was found to be more susceptible to both radio-oxidation and biodegradation. It was observed that in case of ethylene-propylene copolymers, extent of gamma-sterilisation and/or biodegradation depends on the composition and distribution of comonomers. Important surface erosion was detected by SEM, for higher sterilisation doses, after composting. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Biodegradation; chain scission; Composting and fungal culture; gamma-sterilisation; Polyolefins

Photo-bio-degradability of agro waste and ethylene-propylene copolymers composites under abiotic and biotic environments - Kumar, A. Pratheep; Pandey, Jitendra K.; Kumar, Bijendra; Singh, R. P. (Journal of Polymers and the Environment, 2006)
Composites were prepared by two methods, (i) graft copolymerization (GFC) of isotactic polypropylene (PP) with maliec anhydride, (MAH) followed by esterification with coir fiber and (ii) by direct reactive mixing (DFC) of polypropylene (PP) and ethylene-propylene (EP) copolymers with MAH and peroxide with coir fiber. These composites, after molding in films (5 x 5 cm, - 100 mu m thickness) were examined for susceptibility to biological attack by measuring the percentage weight loss in compost upto 6 months, periodically, and fungal colonization on surface of the samples, when kept as sole carbon source for the growth of Aspergillus niger in culture medium upto 40 days. Photodegradation was evaluated by monitoring the variations in FT-IR spectrum and crack formation after successive treatment with UV light (>= 290 nm) for 0, 20, 50 and 100 h at 60 C in the presence of air. Specimens of virgin PP were taken as a reference during all period of photo and biodegradation studies. Significant changes were observed depending on the preparation methods during photodegradation and biodisintegration of composites. DFCs samples were disintegrated faster than GFCs during the composting whereas, in culture, GFCs were covered highly in well uniform way by fungi. It was observed that photo-oxidative ageing directly enhanced the biodegradability of composites as the increase in fungal growth rate and decrease in weight during composting were found. It was concluded that extent of compatibilization had a profound effect on photo-oxidation and biodisintegration of composite material; consequently ester bonds were main units during fungal consumption. Composition of monomers in copolymers was also showing significant effect on the degradability which decreased with increasing content of ethylene in ethylene-propylene (EP) copolymers.
Keywords: Biodegradation; biodisintegration and composting; composites; ethylene-propylene copolymers; photo-degradation

Rapid and high biodegradation of phenols catalyzed by Candida tropicalis NCIM 3556 cells - Varma, Rita J.; Gaikwad, Bhaskar G. (Enzyme and Microbial Technology, 2008)
Cells of 19 yeast cultures, belonging to genus Candida were screened for biodegradation of phenol. The cultures procured from NCIM culture collection and were selected so as to contain a representative of varied strains of the species. These were grown in MGYP3 medium and tested for biodegradation of phenol. C. tropicalis (CT) nos. 3118, 3556 and C. lipolytica 3472 effectively degraded >90% 2 g l(-1) phenol. The C. tropicalis 3556 strain was selected for further studies as it metabolized >95% phenol in just 16 h as compared to the other two which took 48 h. The maximum substrate concentration that could be completely degraded was 2 g l(-1). A study of induction, of different concentration of phenol in the growth medium showed that toxicity to cell growth increased with increasing phenol levels in growth media. Biodegradation of phenol derivatives - o-cresol, m-cresol. 2,6-dimethyl phenol, alpha-naphthol, o-chlorophenol and p-nitrophenol, by the selected three strains indicated that the specificity of each culture varied for different substrate. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Biodegradation; Candida lipolytica; Candida tropicalis; phenol; Phenol derivatives

Biodegradation and phenol tolerance by recycled cells of candida tropicalis NCIM 3556 - Varma, R. J.; Gaikwad, B. G. (International Biodeterioration & Biodegradation, 2009)
Resting cells of Candida tropicalis NCIM 3556 rapidly degraded almost completely 2 g L(-1) phenol in 16h. In this study, we explored the possibility of further increasing the efficiency of the culture by repeatedly reusing the cell for biodegradation. The effect of continuous recycling of whole cells of C. tropicalis, for biodegradation of phenol indicated that though with each recycle of the cell there was steady decline in phenol biodegradation the conversion was appreciable for five recycle (similar to 70%) and reached half-life of 50% after eleven recycles. Inhibition due to substrate, recycling of cells and adaptation of residual cell were estimated and an equation derived; which indicated that the cell resilience to phenol increased with each cycle and at the end of eleven recycle adaptation was 68%. However, when the adapted cells were sub cultured and showed marginal increase <10% in biodegradation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Biodegradation; Candida tropicalis; Inhibition; phenol; Recycle; Tolerance

Continuous phenol biodegradation in a simple packed bed bioreactor of calcium alginate-immobilized Candida tropicalis (NCIM 3556) - Varma, R. J.; Gaikwad, B. G. (World Journal of Microbiology & Biotechnology, 2010)
Phenol biodegradation in a continuous system of immobilized Candida tropicalis NCIM 3556 was studied. The bioreactor was simple, it had a feed inlet from the bottom and the effluent outlet from top, no supplementary oxygen was supplied, the reactor was operated continuously for 116 days. Initially the column was run continuously with a feed concentration of 2 g l(-1) for 42 days whence a degradation of > 97% was achieved. The feed concentration was then increased to 3 g l(-1), for which a similar to 80% biodegradation was sustained for 90 days after which there was a steady decrease in the performance. When the phenol degradation was reduced to similar to 50% in 116 days, the reactor was stopped. The efficiency of free cells recycled every 24 h and immobilized cells were compared; it was estimated that repeated reuse of free cells in batch mode gave an overall efficiency of 0.102 g phenol degradation g(-1) cell wet weight in 12 days. In contrast, the immobilized system of the same biomass had a longer working lifetime of similar to 4 months indicating an efficiency of 3.72 g phenol g(-1) cell wet wt.
Keywords: Biodegradation; Ca alginate; Candida tropicalis; Immobilization; phenol

Effect of gamma-dose rate on biodegradation of gamma-sterilized biomedical polyolefins - Alariqi, Sameh A. S.; Singh, R. P. (Journal of Polymers and the Environment, 2010)
The aim of the present study is to study the effect of gamma-dose rate on the biodegradation of gamma-sterilized polyolefins. Films of isotactic polypropylene, high density polyethylene and ethylene-propylene (EP) copolymer were sterilized under gamma-radiation with doses of 10 and 25 kGy. Two different (60)Co sources were used with dose rate 600 and 780 Gy h(-1). Neat and sterilized samples were incubated in compost and fungal culture environments. The changes in functional groups, surface morphology and intrinsic viscosity in polymer chains were characterized by FT-IR spectroscopy, SEM and viscometric measurements, respectively. It was observed that both gamma-degradation and biodegradation processes depend on the dose rate of gamma-source. It was found that the biodegradation of gamma-sterilized polyolefins in composting and microbial culture environments increased with decreasing the gamma-dose rate.
Keywords: Biodegradation; Composting and fungal culture; gamma-Dose rate; Polyolefins; Sterilization

Biodegradation of chlorobenzene and chlorophenols by pseudomonas cultures - Bhaskar, Gaikwad G.; Rita, Varma J. (Research Journal of Chemistry and Environment, 2013)
Cultures from NCIM culture collection (National Chemical Laboratory, Pune, India) were screened for biodegradation chlorobenzene (CB). A strain, Pseudomonas sp. NCIM 2303, was found to be most effective. The biodegradation was carried out in aqueous solution by resting cells. The decomposition of 0.02% CB was 96.64% in 24h. We have screened cultures for biodegradation of o-chlorophenol and p-chlorophenol. Pseudomonas sp. NCIM 2668 has shown 94.59% degradation of 0.15% o-chlorophenol. Pseudomonas sp. NCIM 2668 has shown 31.42% degradation of 0.2% p-chlorophenol.
Keywords: Biodegradation; chloride; chlorobenzene; etc.; pollution; Pseudomonas sp

Biodegradation of mixed polycyclic aromatic hydrocarbons by pure and mixed cultures of biosurfactant producing thermophilic and thermo-tolerant bacteria - Mehetre, Gajanan T.; Dastager, Syed G.; Dharne, Mahesh S. (Science of the Total Environment, 2019)
Applicability of thermophilic and thereto-tolerant microorganisms for biodegradation of polycyclic aromatic hydrocarbons (PAHs) with low water solubility is an interesting strategy for improving the biodegradation efficiency. In this study, we evaluated utility of thermophilic and thermo-tolerant bacteria isolated from Unkeshwar hot spring (India) for biodegradation of four different PAHs. Water samples were enriched in mineral salt medium (MSM) containing a mixture of four PAHs compounds (anthracene: ANT, fluorene: FLU, phenanthrenc: PHE and pyrene: PYR) at 37 degrees C and 50 degrees C. After growth based screening, four potent strains obtained which were identified as Aeribacillus pallidus (UCPS2), Bacillus axarquiensis (UCPD1), Bacillus siamensis (GHP76) and Bacillus subtilis subsp. inaquosorum (U277) based on the 16S rRNA gene sequence analysis. Degradation of mixed PAH compounds was evaluated by pure as well as mixed cultures under shake flask conditions using MSM supplemented with 200 mg/L concentration of PAHs (50 mg/L of each compound) for 15 days at 37 degrees C and 50 degrees C. A relatively higher degradation of ANT (92% - 96%), FLU (83% - 86%), PHE (16% - 54%) and PYR (51% - 71%) was achieved at 50 degrees C by Aeribacillus sp. (UCPS2) and mixed culture. Furthermore, crude oil was used as a substrate to study the degradation of same PAHs using these organisms which also revealed with similar results with the higher degradation at 50 degrees C. Interestingly, PAH-degrading strains were also positive for biosurfactant production. Biosurfactants were identified as the variants of surfactins (lipopeptide biosurfactants) based on analytical tools and phylogenetic analysis of the surfactin genes. Overall, this study has shown that hot spring microbes may have a potential for PAHs degradation and also biosurfactant production at a higher temperature, which could provide a novel perspective for removal of PAHs residues from oil contaminated sites. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Biodegradation; Biosurfactants; Crude oil; Mixed culture; PAHs; Thermophiles

Enzymatic biodegradation of used engine oil using a novel lipase derived from renewable feedstocks - Tracy, Preetanshika; Dasgupta, Diptarka; Ashok, Patel Pratima; More, Snehal; Sarkar, Bipul; Porwal, Jyoti; Tripathi, Deependra (World Journal of Microbiology & Biotechnology, 2025)
This study introduces an eco-friendly enzymatic approach for biodegrading used engine oil, utilizing a novel lipase from the mesophilic yeast strain Pichia Caribbica. The yeast was cultured in detoxified corncob hydrolysate with used cooking oil as an inducer. OVAT study confirmed that the optimal pH and temperature for lipase production by the strain was 7.0 and 25 degrees Celsius, respectively, with lipase activity of 70 IU/mL. The enzyme effectively degraded similar to 46% of used engine oil over a period of 15 days. Gas Chromatography-Mass Spectrometry (GC-MS) and FT-IR analysis confirmed a significant reduction in hydrocarbon concentrations and the emergence of new functional groups, confirming the enzyme's ability to degrade complex hydrocarbons into less toxic derivatives. These findings highlight the lipase's potential as an effective biocatalyst for eco-friendly bioremediation of oil-contaminated environments, such as soils and aquatic systems, while also emphasizing its role in environmental management through the reuse of waste by-products in enzyme production, thus reducing the environmental impact of improper waste disposal.
Keywords: Biodegradation; Lipase; PC5703; Used cooking oil; Used engine oil

Green synthesis of PLGA and fabrication of topotecan and thymoquinone dual anticancer drug loaded PLGA nanoparticles: a controlled release study for cancer therapy - Srilatha Cheekuramelli, Naga; Muhammed, Hasin N.; Garnaik, Baijayantimala; Sukumaran Nair, Kiran (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2026)
Cancer therapy is often hindered by poor solubility, low bioavailability, drug resistance, and tumor microenvironmental barriers associated with conventional chemotherapeutics. Polymeric nano-drug delivery systems offer a promising strategy to overcome these limitations, particularly for synergistic multi-drug delivery. In this study, a biodegradable and biocompatible PLGA copolymer (70:30, M-w approximate to 14,500) was synthesized by ring-opening polymerization using zinc proline complex as an initiator through a green route. The copolymer's potential for delivering topotecan (TPT), a water-soluble chemotherapeutic, thymoquinone (TQ), a poorly water-soluble chemotherapeutic, and their combination (TPT+TQ) for cancer treatment was investigated. These nanoparticles demonstrateda consistent particle size < 200 nm high encapsulation efficiency along with desirable controlled-release attributes. Moreover, they exhibited specific release characteristics and cytotoxic effects against HeLa cells, achieving an IC50 value of 20.88 M for the combination therapy (TPT+TQ). Additionally, cytocompatibility testing on L929 fibroblasts confirmed over 98% cell viability for blank PLGA nanoparticles. Additionally, confocal imaging studies confirmed efficient cellular uptake and nuclear localization of the nanoparticles. Overall, the PLGA based dual drug loaded nanoparticles presents a promising approach for targeted, synergistic co-delivery, potentially improving efficacy and reducing toxicity in cancer therapy.
Keywords: Biodegradation; dual drug-loading; PLGA copolymer; thymoquinone; Topotecan

Novel biosurfactant assisted biodegradation of polystyrene by Actinomycetes and its chemical understanding - Sakpal, Amrapali; Haq, Nazrul; Dasgupta, Santanu; Alanazi, Fars; Alsarra, Ibrahim A.; Alam, Mahboob; Dastager, Syed G. (Polymer Degradation and Stability, 2026)
The current study highlights the effective biodegradation of polystyrene by two actinobacterial strains, Glutamicibacter sp. K-1 and Rhodococcus sp. BG-30. FT-IR, Raman spectroscopy, and GPC data showed the degradation pattern of polystyrene. Additionally, GC-MS analysis showed that strain K-1 produced a variety of degradation by-products, including alkanes, 2,4-Di-ter-butyl phenol, 2-propenoic acid, tridecyl ester, and dibutyl phthalate, while strain BG-30 produced a greater amount of alkenes, phthalic acid, and isobutyl octyl esters. GPC detected a drop in polystyrene's average molecular weight (Mn), which suggests chain scission of the polymer. Changes in polystyrene's roughness and other morphological properties were shown by AFM and FE-SEM. The effects of a conventional rhamnolipid and a novel thermostable biosurfactant fatty alkene (0.1 % each) on the breakdown of polystyrene were examined. Strain K-1 and BG-30 resulted in increasing the degradation of polystyrene to 12 % (w/w) and 16 % (w/w), respectively in the presence of fatty alkene biosurfactant, there was 10 % (w/w) and 8 % (w/w), degradation in presence of rhamnolipid. To the best of our knowledge, degradation of polystyrene by Glutamicibacter sp. has been reported as a newly identified strain and use of a novel biosurfactant together revealed their potential in biodegradation of plastic to mitigate the plastic pollution using microbial resources.
Keywords: Biodegradation; Fatty alkene biosurfactant; Glutamicibacter sp.; Polystyrene; Rhamnolipid; Rhodococcus sp.